Assessing the research efficiency of higher education institutions in Chile: a data envelopment analysis approach. Issue 6 (8th August 2016) - Munoz, David Andres
Abstract : Purpose: The purpose of this paper is to assess the research efficiency of the Chilean higher education institutions. As it has been argued in the literature, universities in Chile are far from being considered research-oriented institutions. Current governmental reforms have put pressures on the efficient use of public resources, especially, public expenditures in higher education. In response, the proposed data-driven approach can be used to inform educational managers and policy makers about research efficiency. Therefore, a better allocation of the scarce educational resources can be achieved. Design/methodology/approach: Data envelopment analysis (DEA) is used to assess the research efficiency of a set of Chilean universities. Four models are proposed based on different parameters to cover various drivers of the research productivity. Findings: The article provides evidence that only a few universities in Chile are efficient in regards to research. Moreover, interesting results in terms of the differences in efficiency between traditional universities and private universities were found. Universities with a mixed-funding structure (private traditional) are more efficient than both public and purely private universities. Additionally, universities that receive direct funds from the government are on average 3.3 times more efficient than private universities. According to the models, only one private university appeared at the top 10 based on the research efficiency ranking. Practical implications: Current pressures in the funding structures of the higher education system have led to an increased awareness in the utilization of resources. The results provided in this study are useful for guiding a better allocation of public resources and providing insights about efficient funding structures. Originality/value: An understanding of the current status of research efficiency and the identification of the best performers allows educational managers to improve their resource allocation processes.